Holocene paleoclimatic and paleohydrological changesin in the Sárrét basin, NW Hungary - Sümegi, Pál (Documenta Praehistorica, 2008)
According to detailed sedimentological and paleontological analyses carried out on samples taken from the Sárrét-Nádasdladány core-profile, a complete environmental history of a neotectonic depression was drawn. The sequence is composed of fluvial-lacustrine and marshland deposits which started to accumulate during the Late Glacial and culminated at the beginning of the Holocene. The highly characteristic changes in the biofacies were linked to changes in the lithofacies within this sequence. A transition in the dominance of moving water species, observable initially in lacustrine species preferring well-lit, well-oxygenated conditions was observed. Eventually, the littoral and eutrophic lacustrine species, as well as marsh-dwellers, became dominant in the profile, marking the emergence of uniform peat land in the Sárrét Basin.
Keywords: paleontologija; paleontology; paleoekologija; sedimenti; holocen; fosili; mehkužci